Reversal of typical processing dynamics in positive and negative priming using a non-dominant to dominant cross-language lexical manipulation. Issue 6 (3rd July 2019) - Neumann, Ewald; Nkrumah, Ivy K.
ABSTRACT: A bilingual primed lexical decision task was used to investigate priming effects produced by attended and ignored words. Participants were required to name prime target words in their weaker (L2) language and then make lexical decisions to probe target items in their dominant (L1) language. Accelerated lexical decisions to probe target words resulted when the word was a translation equivalent of the preceding prime target word, but they were not impaired when the word was a translation equivalent of the preceding ignored nontarget word. This novel finding of a positive priming effect coupled with the absence of a negative priming effect is the opposite pattern of earlier cross-language experiments wherein priming was assessed from L1 to L2 [i.e., Li, Neumann, & Chen, 2017. Identity and semantic negative priming in rapid serial visual presentation streams. Attention, Perception & Psychophysics, 79, 1755–1776; Neumann, McCloskey, & Felio, 1999. Cross-language positive priming disappears, negative priming does not: evidence for two sources of selective inhibition. Memory & Cognition, 27, 1051–1063; Nkrumah & Neumann, 2018. Cross-language negative priming remains intact, while positive priming disappears: evidence for two sources of selective inhibition. Journal of Cognitive Psychology, 3, 1–12]. The present results may be a reflection of altered excitatory and inhibitory dynamics when a weaker, non-dominant language is the source for potential positive and negative priming effects between languages in bilinguals.